MAY 5, 2015 SOLAR FLARE DATA ANALYSIS IN SUNPY - A. Sarsembayeva,; M. Odsuren,; F. Belisarova,; A. Sarsembay, (Academic Scientific Journal of Computer Science, 2019)
In this paper was monitored solar flare registered on May 5, 2015. This flare, which peaked at 6:11 pm EDT from a sunspot called Active Region 2339 (AR2339), is classified as an X2.7-class flare. We have performed solar data analysis using the Python/SunPy tool. SunPy was chosen as the principle data analysis environment since it provides easy to use interfaces to the Virtual Solar Observatory (VSO)